Using word search puzzle in improving students’ English vocabulary: A systematic literature review - Tira Nur Fitria (Politeknik Negeri Jember, 2023)
Recently, learning activities based on Word Search Puzzles have become a trend inteaching and learning. These activities are believed to increase students' vocabulary.This study reviews the use of Word Search Puzzles in improving students’ vocabulary.The analysis includes 25 relevant papers that meet the required criteria, and the findingsare summarized in the table. These papers answer four main QA (Question-Answer)regarding the effectiveness of Word Search Puzzles in enhancing the students’vocabulary. All 25 papers have a similar research focus, which is related to theeffectiveness of Word Search Puzzles in improving/increasing/enhancing students’vocabulary. All papers use experimental research methods to know the effect of thecomparison of two learning media by using Word Search Puzzle and other learningmedia. Two comparisons this learning media uses control class and experiment class. Acomparison was made of the results of the improvement and mastery of students'vocabulary. It shows that Word Search Puzzle is effective in improving students'vocabulary mastery. This can be seen from the scores of the pretest to posttest in thecontrol and experimental class. There is a significant difference between theexperimental class's pre-band post-test mean scores. Further research is neededconsidering that Word Search Puzzles can be applied in all fields of science.